UNIVERSAL DESIGN FOR LEARNING: THE APPLICATION OF THE COLOR BLIND ALPHABET (Isagoge - Journal of Humanities and Social Sciences, 2021)
Universal Design for Learning stands at the forefront of educational policy  to create universal access to educational curricula for all students, including students with special needs. The ColorADD system is a universal language, describing the three main colors, blue, yellow and red with simple graphic symbols, which, through coding and addition combinations, can associate and record the entire color palette.  The ColorADD  recognition system developed by Dr. Miguel Neiva. Τhe application of a color code alphabet in very essential. It can be used in many sectors, such as music education, and  will concern  education and  educational integration policy, but also the global community with various applications for various aspects of human activities.
Keywords: Universal design; Special needs; Color blind alphabet; ColorADD